Terrific [videorecording (DVD)] - Agee, Jon; Heyborne, Kirby (Dreamscape Media Llc, 2014)
'Terrific,' says Eugene, after winning an all-expenses-paid vacation in Bermuda. 'I'll probably get a really nasty sunburn.' Unfortunately, Eugene's luck is a lot worse than that. First, his cruise ship sinks, then he ends up stranded on a tiny island. But Eugene isn't alone. There's another castaway, a parrot with a busted wing, who tells him what there is to eat and drink and how to build a sailboat. Cranky Eugene pays attention, and his luck begins to change.